A PERSONALITY AND BIG FIVE FACTOR MODELS OF PERSONALITY - Sabani, Havva (International Scientific Journal Vision, 2018)
This article aims to describe the most salient features of personality and explain how these big five factors play a role in personalities. The search for the structure of personality is as old as the study of human nature itself. Within the last two decades, there has been consensus within the organization behavior researchers that five factor model of personality, often termed the “big five” personality frame work (Goldberg, 1981, 1990; Costa and McCrae, 1992; John and Srivastava, 1999), is one of the most prominent models in contemporary psychology to describe the most salient features of personality. Understanding and studying personality allows psychologists to predict how people will respond to the sort of things they prefer and value. A number of different theories have emerged to explain various aspect of personality.Personality is often described in terms of traits. Since the mid-20th Century, psychologists have attempted to understand personality differences using with reference to these personality traits. Today the “Big Five” Theory is the most popular and widely accepted trait theory of personality. The big five personality dimensions can be divided into five factors: Extraversion, agreeableness, conscientiousness, openness, and neuroticism.